1980
DOI: 10.1104/pp.65.6.1149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature, Water Potential, and Light on Germination Responses of Redroot Pigweed Seeds to Ethylene

Abstract: The responses of redroot pigweed (Amaranthus retrojixus L.) seeds to nine ethylene concentrations between 0.5 and 50 microlters per liter were assessed at different temperatures and water potentials and in either continuous white ight or darkness. Under all experimental treatments, the probit-transformed percentages increased inearly with the log of the ethylene concentration. In dormant seeds, the slope of the response line was unaffected by either light or water potential but increased with decreasing temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…the same trend observed in wild oat. Schonbeck & Egley (1980) found that the germination rate of dormant redroot pigweed seeds ( Amaranthus retroflexus L.) was more rapid at 25°C than at 40°C. Mares & Ellison (1989) found that freshly harvested dormant wheat grains did not germinate when imbibed at temperatures of 20°C or higher.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…the same trend observed in wild oat. Schonbeck & Egley (1980) found that the germination rate of dormant redroot pigweed seeds ( Amaranthus retroflexus L.) was more rapid at 25°C than at 40°C. Mares & Ellison (1989) found that freshly harvested dormant wheat grains did not germinate when imbibed at temperatures of 20°C or higher.…”
Section: Discussionsupporting
confidence: 60%
“…Cumulative germination percentages from an F 1 population incubated at 10, 15, 20 and 25°C were analysed by probit analysis ( Finney, 1971, pp. 20–30) using the methods described by Schonbeck & Egley (1980). Germination percentages were transformed to probits that result in log‐linear curves for seed populations that are normally distributed.…”
Section: Methodsmentioning
confidence: 99%
“…2), it was not surprising that temperature changes during this period affected the ethylene inhibition most. Effects of temperature on ethylene-stimulated germination also have been noted by Schonbeck and Egley (6). Alternations of 20 (16 h) to 30°C (8 h) greatly reduced the inhibition (Fig.…”
Section: Resultsmentioning
confidence: 58%
“…Anthophyta: 3, Avena fatua seed (Adkins et al, 1984a(Adkins et al, , b, 1985Cairns and De Villiers, 1986); 4, Avena sativa seed (Corbineau et al, 1991); 5, Echinochloa crus-galli seed (Taylorson, 1988;Leather et al, 1992); 6, Hordeum vulgare seed (Hareland and Madson, 1989;Fontaine et al, 1994); 7, Oryza sativa seed (Tseng, 1964;Major and Roberts, 1968;Cohn et al, 1983Cohn et al, , 1987Cohn et al, , 1989Cohn and Castle, 1984;Cohn and Hughes, 1986); 8, Panicum capillare seed (Taylorson, 1989); 9, Panicum dichotomiflorum seed (Taylorson and Hendricks, 1979;Taylorson, 1980); 10, Amaranthus albus seed (Hendricks and Taylorson, 1974;Taylorson, 1979); 11, Amaranthus retroflexus seed (Taylorson, 1979(Taylorson, , 1989Schonbeck and Egley, 1980); 12 Berbera verna seed (Hendricks and Taylorson, 1974); 13, Lactuca sativa seed (Brooks et al, 1985;Abeles, 1986); 14, Portulaca oleracea seed (Taylorson, 1979); 15, Rumex acetosella seed (French and Leather, 1979); 16. Rumex crispus seed (French and Leather, 1979;Taylorson, 1984;French et al, 1986).…”
Section: Plantaementioning
confidence: 99%